Pembelajaran Sains di Madrasah Berbasis Tradisi Islam (Gerak Benda Menurut Ibn Bajah) - Dalilah Nur Alip; Ade Putri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Many works by Muslim scientists that have not been used as science teaching materials in Islamic schools (madrasah), generally the teaching materials given at the Islamic schools (madrasah) are the same as the teaching materials given in high school. This writing aims to uncover the findings of Muslim scientists who can be used as science teaching materials in Islamic schools (madrasah). The method of discussion used in this paper is the history of science with an Islamic perspective and demonstrative science learning methods. Data is collected through literature. The results of the study revealed that the motion theory of Ibn Bajah that influenced Galileo Galilei could be taught in Islamic schools (madrasah). The aim is to enrich students' insight into the Islamic perspective.